2002
DOI: 10.1080/0144361021000020349
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the use of antenatal and obstetric care services in rural Kano, Nigeria

Abstract: The objective of this study was to identify the sociocultural and economic factors that act as barriers to women's use of antenatal care services and hospital delivery in a rural community in Kano State, Northern Nigeria. The study was based on an interview of 107 pregnant women conducted by a trained midwife in the native language of the area. Findings indicate that the majority of women (88%) (CI = 81.8-94.2%) in the study area did not attend for antenatal care, and 96.3% (CI = 93.0-99.8%) had delivered or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
122
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 5 publications
12
122
3
Order By: Relevance
“…In general, poor pregnancy outcome has been reported to be common among pregnant women with low use of ANC and delivery services [20,21]. In Nigeria, the low rate of ANC and delivery was partly due to cultural factors such as ethnicity and religious beliefs [22,23] and low level of female autonomy which is driven by religion and ethnic beliefs [24][25][26]. The role of ANC in averting pregnancy related deaths and other forms of poor pregnancy outcomes such as vesico-vaginal fistula was further underscored by WHO in late 2016 that the recommended number of ANC visits should now be at least 8 instead of 4 for optimal pregnancy outcomes [27].…”
mentioning
confidence: 99%
“…In general, poor pregnancy outcome has been reported to be common among pregnant women with low use of ANC and delivery services [20,21]. In Nigeria, the low rate of ANC and delivery was partly due to cultural factors such as ethnicity and religious beliefs [22,23] and low level of female autonomy which is driven by religion and ethnic beliefs [24][25][26]. The role of ANC in averting pregnancy related deaths and other forms of poor pregnancy outcomes such as vesico-vaginal fistula was further underscored by WHO in late 2016 that the recommended number of ANC visits should now be at least 8 instead of 4 for optimal pregnancy outcomes [27].…”
mentioning
confidence: 99%
“…Similarly, the Pakistani study underscored that generally women have freedom to go out of their matrimonial homes as part of social obligation within the family and neighbourhood structure and therefore not a valid measure for autonomy [9,27]. However, this assertion is invariance with a study in rural parts of Kano state Nigeria, where women are kept in seclusion and go out of their matrimonial homes after getting permission from her spouse or other elderly family member irrespective of the need for her to go out [28]. Overall this indicates the freedom of movement by married women as a variable to assess her level of autonomy showed variation among cultures of different parts of the world.…”
Section: Discussionmentioning
confidence: 74%
“…Overall this indicates the freedom of movement by married women as a variable to assess her level of autonomy showed variation among cultures of different parts of the world. Several studies have been reported on the poor use of MHS in East [18,29] and West [28,[30][31][32][33][34] African countries had indirectly suggested significant proportion of women are fully dependent on their husband and family in order to pay for services rendered in health facilities. By extension the authors in our opinion have indicated that, these women lack financial independence, incapable to decide on where and when to go and to get medical services as they are dependent on financial and mind set of whoever is going to pay their health bills.…”
Section: Discussionmentioning
confidence: 99%
“…This study, like others, revealed rural women place significant value to birthing position during labour and delivery [3,25,26] . In rural northern Nigeria, women decided against hospital delivery due to inability to adopt squatting posture, the perceived lack of privacy, and presence of a male staff attendant [3] . The women also expressed difficulty with payment for services in the hospital as a factor that hinders them from hospital delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, maternal mortality ratio (MMR) remains unacceptably high [2,3] with approximately 54,000 women and girls dying each www.jmscr.igmpublication.org Impact Factor (SJIF): 6.379 Index Copernicus Value: 71.58 ISSN (e)-2347-176x ISSN (p) 2455-0450 DOI: https://dx.doi.org/10.18535/jmscr/v6i2.32 year due to preventable pregnancy-related complications [4] . Similarly, high perinatal mortality rate (PMR) resulting from unattended births or unskilled attendants at delivery has been documented to be a refractory problem in many parts of the country [5,6] .…”
Section: Introductionmentioning
confidence: 99%